Prognostic Significance of the Neutrophil-to-Lymphocyte Ratio in Patients with Non-Muscle Invasive Bladder Cancer treated with Intravesical Bacillus Calmette–Guérin and the Relationship with the CUETO Scoring Model: Significance of the NLR with CUETO model - Chung, Jae-Wook; Kim, Jin Woo; Lee, Eun Hye; Chun , So Young; Park, Dong Jin; Byeon, Kyeong Hyeon; Choi, Seock Hwan; Lee, Jun Nyung; Kim, Bum Soo; Kim, Hyun Tae; et al. (Urology Journal, 2021)
Purpose: In this study, we evaluated the predictability of a modified Club Urológico Español de Tratamiento Oncológico (CUETO) scoring model and preoperative neutrophil-to-lymphocyte ratio (NLR) in patients with non-muscle invasive bladder cancer (NMIBC). Materials and Methods: From August 2005 to May 2016, a total of 281 patients received intravesical bacillus Calmette–Guérin therapy after transurethral resection of a bladder tumor. The pathologic stage of all patients was Ta or T1. Of 281 patients, 84 (29.9%) experienced recurrence and 14 (5.0%) developed progression. The mean follow-up period was 46 months. The cut-off value for NLRs was 2.29. Results: One hundred-eight patients (38.4%) displayed a high NLR (> 2.29). In Kaplan–Meier curve analysis, a high NLR was associated with lower recurrence-free survival (RFS) (P < .001) and progression-free survival (PFS) (P = .002). CUETO scores were associated with RFS (P < .001), but not with PFS (P = .423). A combination of NLRs and the CUETO risk model correlated with RFS (P < .001) and PFS (P = .002). In multivariate analysis, female gender, concomitant carcinoma in situ (CIS), tumor number >3, recurrent tumors, and a high NLR were independent factors predicting recurrence (all P < .05). Concomitant CIS, recurrent tumors, and a high NLR were independent factors for predicting progression (all P < .05). Conclusion: In patients with NMIBC, an NLR >2.29 was identified as a significant factor for predicting tumor recurrence and progression. Inclusion of preoperative NLR enhanced the accuracy of the CUETO model to predict disease progression.